Civic Association and Des-Institutionalization of Political Parties in Ecuador: Breaks and Continuities, 1979-2014 - Basabe-Serrano, Santiago (Política y Sociedad, 2016)
This article examines the relationship between civic association and the party politics institutionalization. Regardless of the theoretical approaches that focus on endogenous factors to the political institutions or normative variables, I point out that the strength of the citizen organizations is a key variable to evaluate the level of the party politics institutionalization. So, the presence of stable citizen associations with specific demands would incentive the emergence of consolidated political parties in the electoral arena. On the other side, the lack of strong citizen associations would drive that political parties be formed as electoral machines. Supported by historical narratives and electoral results in Ecuador between 1979 and 2014, the article confirms that when the citizen association is structurally weak, the probabilities of the emergence of less institutionalized political parties increases.